GE11 : analysis of strut forces for braced excavation in stiff clay - Ng, Peng Han (2014)
Finite element analyses using Plaxis 2D were carried out to evaluate the effects of various design parameters on strut forces for braced excavation in stiff clay deposits. The design parameters to be analysed includes wall stiffness, depth to hard stratum, depth of embedment, stiffness of wall and the shear strength of soil. The results of the strut loads obtained from the FEM analysis will be compared with Peck‟s Apparent Pressure Diagram (APD).